ABADI AYAM ORGANIC NUTRITION CHICKEN TO HALAL MARKET: BUSINESS PLAN - YONG, JIA PEY (Research in Management of Technology and Business, 2023)
The main objective of the business development plan is to bring the vision and description of the operation and strategy of organic nutritious chicken to the halal market to full potential in order to achieve this objective, to conducts the theoretical framework and empirical part about the organic food marketing plan. In the theoretical part, to starts with the concept of organic farming and organic food. The definition and characteristics of the organic food is reviewed from various sources of literature. To identify the factors, affect the development of the organic market, key issues from earlier studies as well as marketing environment analysis is applied. The study of the marketing environment includes the analysis of the macroenvironment, microenvironment and internal analysis. Then the model of the marketing mix to propose the business plan for the Abadi Ayam. The situation of the industry and the Abadi Ayam Sdn. Bhd are analysed in the empirical part. Finally, this business plan recommended marketing action plan will help Abadi Ayam Sdn. Bhd. gain the source of finance that would be used by the new business is financial industry or agency that Abadi Ayam applies to it for financial support. Malaysia Halal market to establish and operate halal organic chicken for target regions and customers, in order to provide the business with a clear direction. The following section defines the business concepts that will be used to expand their marketing chain to the Halal Market, a deeper dive into the company’s ideology, mission, vision, and related products.